Fluxos e entre fluxos: metamorfoses de um corpo - Heine, Gabriela Massarra Santos (2018)
The present research results from a desire to seek other forms of relationship with the other, to see and feel it. In this sense, the emphasis of our object of study falls on the writings of the contemporary philosopher, Gilles Deleuze, in his readings in Espinosa and we search for possible connections with Jose Gil and Kuniichi Uno. It is, therefore, to think of human complexity in what it possesses of more particular: the potency of its body. Dance is proposed as a means of metamorphosis of the body and is consequently not the only form. To think about some flows and between flows that guide and permeate the Deleuze’s thought is like a kind of walk between transform and the conductor would be the body. In dance there are affectations capable of promoting the increase of power, strengthening our conservation as being. The more fit the body is, the greater will be your known its relation to the world. Thus, we seek through this dissertation to think about the relation of philosophy to dance, to literature, to theater. We understand that life is that of the body and what happens in it resounds in thought